2014
DOI: 10.1111/1574-6941.12272
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of small-scale variation in the size and composition of phenanthrene-degrader populations and PAH contaminants in traffic-impacted topsoil

Abstract: Small-scale colocalisation of microbial polycyclic aromatic hydrocarbon (PAH) degraders and PAHs in contaminated soil is a prerequisite for efficient biodegradation of the PAHs. We therefore tested the hypothesis that phenanthrene-degrading bacteria are colocalised with PAHs at the millimetre-to-centimetre-scale. Microbial populations and PAH concentrations were determined for 40-mg samples from a 112-mm transect of a traffic-impacted topsoil. The spatial distribution of cultivable phenanthrene degraders (0.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…In our study, centimeter-scale mapping revealed the presence of hotspots of PAH-degrading bacteria and of PAH content, but there was no obvious correlation between these two parameters. Similar results were obtained by Johnsen et al (2014) [ 44 ], in a polluted roadside soil at the millimeter- to centimeter-scale. The lack of correlation could be explained by the thorough degradation of the spiked PAH fraction after 37 days, when mapping was performed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, centimeter-scale mapping revealed the presence of hotspots of PAH-degrading bacteria and of PAH content, but there was no obvious correlation between these two parameters. Similar results were obtained by Johnsen et al (2014) [ 44 ], in a polluted roadside soil at the millimeter- to centimeter-scale. The lack of correlation could be explained by the thorough degradation of the spiked PAH fraction after 37 days, when mapping was performed.…”
Section: Discussionsupporting
confidence: 91%
“…Positive relationships between PAH hotspots and organic carbon concentrations [ 41 ], fungal biomass [ 42 ], bacterial diversity and ring-hydroxylating dioxygenase gene abundance [ 43 ], was established at the meter scale in aged-polluted soils. At finer (millimeter to centimeter) scale in urban roadside soil, the spatial heterogeneity of PAH-mineralization potential [ 3 ] was highlighted, but the distribution of PAHs and PAH-degraders was not correlated [ 44 ]. In contrast, other studies have demonstrated covariation between PAH concentration and spatial pattern of microbial diversity ([ 45 , 46 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Johnsen et al . (), examining a traffic‐impacted soil transect, also found raised levels of a dioxygenase gene associated with actinobacterial degraders, with little proteobacterial representation. In contrast, Louvel et al .…”
Section: Discussionmentioning
confidence: 97%
“…Studies have reported the substantial roles of streets in conveying runoff and discharge of environmental, faecal and antibiotic-resistant bacteria to various surrounding water systems, such as streams (Baral et al, 2018), lakes (Zhang et al, 2016), waterways (Calderon et al, 2017) or groundwater (Voisin et al, 2018). Analyses of soils from a motorway or highly trafficked road in Copenhagen have revealed the presence of microbial polycyclic aromatic hydrocarbon degraders (Johnsen et al, 2006;Johnsen et al, 2014). An analysis of urban soils from the street green belts of the city of Chicago, USA, revealed that soils along a one-way street showed higher Shannon and phylogenetic diversities than other soils, including those along a two-way street, a feature that could be correlated with soil pH, moisture and texture (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%